2013
DOI: 10.1556/oh.2013.29801
|View full text |Cite
|
Sign up to set email alerts
|

Current surgical methods for advanced glaucoma

Abstract: A szerző az előrehaladott glaucomás károsodás esetén hatékony műtéti eljárásokat tekinti át. Magas nyomású, előre-haladott glaucoma esetén alacsony szemnyomás elérése szükséges. Ezt az első műtétként, megfelelő pre-és posztoperatív gyulladásgátló kezelés mellett végzett, mitomycin C-alkalmazással kombinált trabeculectomia biztosítja a legeredményesebben. Sok esetben azonban a glaucomaellenes fi ltrációs műtét sikertelenné válik a fokozott episcleralis hegesedés miatt. Ilyenkor a hosszú elvezetőcsövű csarnokvíz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…TE with antifibrotic agents such as 5-fluorouracil (5-FU) and mitomycin-C (MMC) resulted good IOP decrease and fibrosis suppression response. [5][6][7] Despite all these precautions wound healing response is personal and exaggerated wound healing may cause fibrosis of episcleral tissues even in eyes with low risk and surgery may end up with failure. 8,9 Clinical trials showed that steroids, even in massive doses, could not be relied on to give adequate control of bleb inflammation and fibrosis in all cases.…”
Section: Fibrosis Suppression Therapy In Failed Filtering Blebs Aftermentioning
confidence: 99%
“…TE with antifibrotic agents such as 5-fluorouracil (5-FU) and mitomycin-C (MMC) resulted good IOP decrease and fibrosis suppression response. [5][6][7] Despite all these precautions wound healing response is personal and exaggerated wound healing may cause fibrosis of episcleral tissues even in eyes with low risk and surgery may end up with failure. 8,9 Clinical trials showed that steroids, even in massive doses, could not be relied on to give adequate control of bleb inflammation and fibrosis in all cases.…”
Section: Fibrosis Suppression Therapy In Failed Filtering Blebs Aftermentioning
confidence: 99%